Effects of Defoliants on Seed Germination in Relation to Weeding Periods and Irrigation Regimes (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is revealed that at irrigation scheduling and the methods of topping work on fatness of seeds cotton of a grade “Zarafshan”. At application defoliants UzDEF and PoliDEF fatness of seeds raises in comparison with defoliants LiquidXMD and without the use of de defoliation.